Literature and philosophy in dialogue : essays in German literary theory - Gadamer, Hans-Georg, 1900-2002 (SUNY series in contemporary continental philosophy., 1994)
Hans-Georg Gadamer, the major proponent of philosophical hermeneutics, reveals himself here as a highly sensitive reader and critic of the German literary tradition. This is not the work of a specialist as narrowly defined in the typical literary study. Although he is a master of the techniques of criticism, Gadamer always sees the study of literature as a fundamentally human activity where human beings, generation after generation, pose their questions to an encroaching darkness that threatens to rob them of their confidence in the meaning of life and death. Never pedantic or antiquarian, these studies show such literary giants of the German past as Goethe and Holderlin as our contemporaries. Gadamer demonstrates his ability to achieve the creative interplay of literature and philosophy which, in isolation, easily degenerate into sterile academic games. Typical of this dialogue are essays on Rainer Maria Rilke, including an examination of a problem of punctuation in one of his poems. What would be, in less capable hands, one more solution to a literary problem, turns out to be one of Gadamer's creative approaches to the mystery of man's relation to time and death.